2014
DOI: 10.1371/journal.pone.0088745
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a as a Potential Biomarker in Diagnosis of Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: IntroductionPrevious studies demonstrated that MicroRNA-92a (miR-92a) was significantly differential expressed between colorectal cancer (CRC) patients and control cohorts, which provide timely relevant evidence for miR-92a as a novel promising biomarker in the colorectal cancer patients. This meta-analysis aimed to evaluate potential diagnostic value of plasma miR-92a.MethodsRelevant literatures were collected in PubMed, Embase, Chinese Biomedical Literature Database (CBM), Chinese National Knowledge Infrastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…This agreed with Faltejskova et al [33] who documented evidence against using it in diagnosing and monitoring CRC, contrary to many studies that confirmed its significant role in diagnosing CRC with adequate sensitivity and specificity [11,34,[37][38][39]. Even Huang et al ascertained its role when combined with miR-29a [34].…”
Section: Discussionsupporting
confidence: 73%
“…This agreed with Faltejskova et al [33] who documented evidence against using it in diagnosing and monitoring CRC, contrary to many studies that confirmed its significant role in diagnosing CRC with adequate sensitivity and specificity [11,34,[37][38][39]. Even Huang et al ascertained its role when combined with miR-29a [34].…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have reported that serum and plasma miRNAs may serve as novel biomarkers for various diseases, including T2D (14,(17)(18)(19)(20)(21). Furthermore, miRNAs in peripheral whole blood have also shown promise as a novel class of biomarkers for the detection of several types of cancer, such as brain (22) and breast (23) cancer, as well as acute myocardial infarction (24), and other human diseases (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, changes in single miRNAs and in miRNA signatures have been reported in the serum and plasma of patients with various diseases, such as cancer (17,18) and cardiovascular diseases (19,20). Furthermore, a previous population-based cohort study identified a set of plasma miRNAs that were differentially expressed in patients with T2D and healthy controls (21), and among them, miR-15a was demonstrated to be the most strongly associated with T2D.…”
Section: Introductionmentioning
confidence: 99%
“…furthermore, increasing numbers of mirnas have been observed in various types of cancer and may be involved in modulating cancer cell behavior (8)(9)(10). Several aberrantly expressed mirnas have been proven to be associated with tumorigenesis, tumor progression and metastasis in crc, and taken as prognostic indicators for crc including mir-150 (11), mir-28-5p/-3p (12), mir-200 (13) and many others (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%